Penggunaan Berbagai Medium Tanam dan Konsentrasi Pupuk Organik Cair pada Pertumbuhan dan Produksi Mentimun Jepang (Cucumis sativus) Secara Hidroponik - Fetmi Silvina; Syafrinal ' (Jurnal Sagu, 2008)
The research aimed to look at the impact of interaction between growth medium and fertilizer concentration to the growth and development of the Japanese cucumber (Cucumis sativus). This research was factorial experiment which used Completely Randomized Design. The treatments were: growth medium (M1= sand, M2= hull of rice charcoal, M3= mixed of sand and hull of rice charcoal) and concentration of liquid organic fertilizer “Super Bionic”(P1= 1 cc/1 water, P2= 2 cc/1 water, P3=3 cc/1 water).Parameters observed were plant height, harvest age, fruit number per plant and fruit weight per plant. This research concluded that interaction between mixed growth medium (rice hull and sand) and 3 cc/1 water super bonic concentration indicated better growth and development of plant, and resulted in higher production of Japanese cucumber.